Response of squids to different colours and intensities of artificial light - Ibrahim, Sakri; Hajisamae, Sukree (Universiti Putra Malaysia Press, 1999)
Study on the response of big fin reef squid (Sepioteuthis lessoniana) and mitre squid (Loligo chinensis) to different characteristics of artificial light was conducted in an experimental cage. The response of squids to lights was dete-rmined by its Average Mean Displacement Position (AMDP). The two species responded significantly different to different intensities of light but not to different colours of the light. Sepioteuthis lessoniana preferred a range of undenuater illuminance of 1.5-25.0 lux while Loligo chinensis preferred a range of 1.5-22.5 lux, but peak range for both species was recorded at 2.5-10.0 lux. Sepioteuthis lessoniana has a stronger positive phototactic behaviour than Loligo chinensis. This study provides the knowledge on the behavioural response of squid to artificial light and may pave a way for multi-species as well as species-selective harvesting techniques.